Grafting studies onto cellulose by atom-transfer radical polymerization - Coskun, M; Temüz, MM (Wiley, 2005)
Styrene (Sty), methyl methacrylate (MMA), methacrylamide (MAm) and acrylomorpholine (AcM) were grafted onto powder cellulose by atom-transfer radical polymerization. Cellulose chloroacetate (Cell-ClAc), as a macro-initiator, was first prepared by the reaction of chloroacetyl chloride with primary alcoholic OH groups on powder cellulose. CuBr and 1,2-dipiperidinoethane were used as a transition-metal compound and as a ligand, respectively. These reactions were monitored by FT-IR and weight increase in Cell-ClAc. In case of styrene, although some weight increase occurred, no evidence of grafting could be observed in the FT-IR spectrum, while there were strong evidence of grafting with MMA, MAm and AcM. Cell-graft-MAm, Cell-graft-AcM and Cell-graft-MMA showed new carbonyl bands at 1665, 1640 and 1735 cm(-1), respectively. Dye-uptake and dye-absorption properties of cellulose, for alizarin yellow (basic dye) and bromocresol green (acidic dye), and its moisture- and water-uptake capacities improved with the grafting, but some decrease was observed in thermal stability. (C) 2004 Society of Chemical Industry.
Keywords: graft copolymer; cellulose; atom transfer radical polymerization